Local Radiation Therapy for Palliation in Patients With Multiple Myeloma of the Spine - Mark, Daniel; Gilbo, Philip; Meshrekey, Raymond; Ghaly, Maged (Frontiers in Oncology, 2019)
Purpose: The objective of this study was to assess a contemporary cohort of patients with multiple myeloma referred for palliative radiation to the mobile spine for clinical and radiological responses. Materials/Methods: The records of patients treated between 2009-16 with radiotherapy for multiple myeloma of the spine were retrospectively reviewed. Demographics, systemic therapy, radiation dose, number of fractions, radiographic response based upon adapted RECIST criteria, and symptomatic response were recorded. Results: 88 patients and 98 treatment courses were analyzed. All courses were analyzed for symptomatic response and 61 of the treatment courses were available for radiologic follow-up. The median follow-up was 9.7 months with a median radiation dose of 25 Gy (12.5-50 Gy), and median fractions of 10 (5-25). Fifty-four percent of patients had a high-risk lesion. Symptomatic response as measured by a decrease of decrease of < 5 points on the pain related scale was 83% and 34% of patients had a decrease of > 5 points. Of 35% of patients that had neurologic impairments prior to treatment, improvement was identified 83% of the time. Radiographic response was noted as 13% complete response, 16% partial response, 57% stable disease and 13% disease progression. Specifically, high-risk lesions treated with radiation alone demonstrated no regression with only 10% demonstrating partial response. Conclusion: This retrospective series of patients treated with palliative intent for multiple myeloma using various dose and fractionation schemes showed favorable symptomatic relieve in most patients. Radiographic response did not correlate with clinical response with fewer patients having radiologic disease regression. Longer follow-up is necessary to determine if the lack of radiologic response is associated with clinically relevant recurrent pain.